Maternal nano-selenium and glycyrrhiza extract supplementation improve antioxidant status in sows and promote postnatal growth of IUGR piglets - Yuanfeng Li; Qi Liu; Yan Wang; Xianglei Fu (Reproductive Biology, 2026)

Adaptive mode and controller switching for intelligent motion control of robotic fish with hybrid propulsion system - Fagang Bai; Xianglei Yan; Lei Guo; Yanjun Liu; Xin Pan; Gang Xue (Ocean Engineering, 2026)

Environmental context and human presence at the Shaojiagouwan site, Salawusu River basin - Jiequn Hua; Fuyou Chen; Hao Long; Shuangquan Zhang; Tingting Chen; Yinghua Wang; Mingchao Shan; Han Yang; Shengrui Li; Jiacheng Ma; Jian Wang; Guanhan Chen; et al. (Quaternary Science Reviews, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Anchoring phase change interface enhances solar thermal energy storage - Qiao Xu; Jingwen Zhu; Yan Wang; Xianglei Liu; Tao Wang; Jianguo Wang; Shushan Lv; Yongliang Li (Science Bulletin, 2026)

Interaction pathways of CO, NO2, and PM2.5 on cool season ozone: Insights from data-based model and mechanism-based model - Chang Liu; Yanan Guan; Yajie Suo; Xianglei Zheng; Chenguang Yan; Chenyang Jia; Xiaosong Hou; Jing Yang; Xinxin Ye; Litao Wang; Jiguang Deng; Erhong Duan (Journal of Environmental Sciences, 2026)

Trajectory tracking control of robotic fish in offshore disturbance environments via disturbance observer-based inverse sliding mode - Juntao Sun; Yanjun Liu; Fagang Bai; Xianglei Yan; Enzhi Quan; Gang Xue (Frontiers in Marine Science, 2025)
Considering the complex offshore environment, where small robotic fish are exposed to surface disturbances from wave forces, suspended particles, and model uncertainties, as well as deep-water disturbances from bottom currents, this paper proposes an inverse sliding mode control strategy based on a disturbance observer to enhance trajectory tracking robustness. The research focuses on a tail-fin-driven bionic robotic fish. Utilizing its kinematic and dynamic models, a virtual control law based on an agent dynamics model is proposed, with the tail fin integrated as a real control input. A nonlinear disturbance observer with controllable convergence characteristics is developed to estimate and compensate for disturbances, including wave forces and model uncertainties. Additionally, a velocity error correction function is introduced to mitigate the impact of strong disturbances. Based on Lyapunov theory, an adaptive sliding mode control law is derived to ensure system stability. The control law for the caudal fin swing angle and bias is obtained by inverting the virtual control inputs, applied to the robotic fish’s accurate model. Numerical simulations show that the disturbance observer’s tracking error remains below 5%, and the trajectory tracking error is within 0.1 meters, representing only 2.2% of the robotic fish’s body length. Compared to mainstream control methods, the proposed approach significantly enhances robustness in contrast to the conventional sliding mode control with observers, and exhibits substantially smaller tracking errors, especially during trajectory transitions.

Innovative bio-based double-crosslinked gel foam: Development, characterization, and fire suppression in coal spontaneous combustion - Heng Gao; Bei Li; Yan Li; Xianglei Yuan (Fuel, 2025)

Discovery of key volatile compound and regulatory gene governing the ‘taro-like’ aroma in wax gourd (Benincasa hispida) - Zhikui Cheng; Peng Wang; Liwen Su; Yan Deng; Wenhui Bai; Zhihao Chen; Xianglei Chen; Wenjin Yu; Zhengguo Liu (Food Bioscience, 2024)

Fine mapping and functional validation of the candidate gene BhGA2ox3 for fruit pedicel length in wax gourd (Benincasa hispida) - Yan Deng; Peng Wang; Wenhui Bai; Zhihao Chen; Zhikui Cheng; Liwen Su; Xianglei Chen; Yeshun Bi; Rongjin Feng; Zhengguo Liu (Theoretical and Applied Genetics, 2024)

Resilient performance of self-centering hybrid rocking walls with curved interface under pseudo-static loading - Xing Su; Shi Yan; Xianglei Sun; Tao Wang (Earthquake Engineering and Engineering Vibration, 2024)

Reconstructing the western boundary variability of the Western Pacific Subtropical High over the past 200 years via Chinese cave oxygen isotope records - Jingyao Zhao; Hai Cheng; Yan Yang; Liangcheng Tan; Christoph Spötl; Youfeng Ning; Haiwei Zhang; Xing Cheng; Zhe Sun; Xianglei Li; Hanying Li; Wen Liu; et al. (Climate Dynamics, 2019)